Evaluasi Program Pendidikan Karakter di Sekolah Kristen - Linda Ferdian; Yari Dwikurnaningsih (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2020)
Abstract : The purpose of this study was to evaluate the context, input, process, and product of the character education program at the Kanaan Christian School Semarang. The results showed: (1) Context, Kanaan Christian School Semarang really needs a character education program; (2) Input, character education at the Kanaan Christian School Semarang refers to the School's Vision and Mission and also the 2013 Curriculum (K-13); (3) The process, the implementation of the character education program at the Kanaan Christian School Semarang, the teacher carries out the learning according to the lesson plans that have been made, by adding character education values that are adjusted to the topics contained in basic competencies; (4) Products, the results of the character education program at the Kanaan Christian School Semarang, namely the presence of 5S culture (Greetings, Smiles, Greetings, Polite and Courtesy) and through the character assessment form. Overall, the character education program at the Kanaan Christian School Semarang has fulfilled the program objectives that have been previously set.Abstrak: Tujuan penelitian ini adalah mengevaluasi konteks, masukan, proses, dan produk program pendidikan karakter di Sekolah Kristen Kanaan Semarang. Hasil penelitian menunjukkan: (1) Konteks, Sekolah Kristen Kanaan Semarang sangat membutuhkan program pendidikan karakter; (2) Input, pendidikan karakter di Sekolah Kristen Kanaan Semarang mengacu pada Visi dan Misi Sekolah serta Kurikulum 2013 (K-13); (3) Proses, pelaksanaan program pendidikan karakter di Sekolah Kristen Kanaan Semarang, guru melaksanakan pembelajaran sesuai RPP yang telah dibuat, dengan menambahkan nilai-nilai pendidikan karakter yang disesuaikan dengan topik yang terdapat pada materi pokok. kompetensi; (4) Produk, hasil program pendidikan karakter di Sekolah Kristen Kanaan Semarang yaitu adanya budaya 5S (Salam, Senyum, Salam, Sopan dan Sopan) dan melalui formulir penilaian karakter. Secara keseluruhan, program pendidikan karakter di Sekolah Kristen Kanaan Semarang telah memenuhi tujuan program yang telah ditetapkan sebelumnya.